Issue Notes - , Editor (Historical Papers, 2022)
The following papers were presented to the Canadian Society of Church History, but were not made available for publication: Gordon L. Heath, “Half-Breeds and Rebels: Canadian Baptist Newspapers and Constructions of the Riel Rebellion in 1885″; Marcus Meier, “Jane Leade’s Spiritual Diary ‘A Fountain of Gardens’ – Autobiographical Reflections in the Age of Enlightenment”; Douglas H. Shantz, “The Harvest of Pietist Theology: The Intersection of Mystical Protestantism and Enlightenment Thought in the Autobiography of Friedrich Christoph Oetinger (1702-1782)”; James Robertson, “His Dominion vs. New Ireland: The Ontario Protestant Response to the Fenian Invasion of 1866″; Robynne Rogers Healey, “Putting Peace into Practice: Cold War Quaker Experiments in Civil Defense”; James Enns, “Saving Germany: North American Mennonite Missionaries in the Post-War Protestant Heartland”; Brian Froese, “‘Our Christians’: Mennonite Missions and Cultural Encounters in British Columbia”; and Royden Loewen, “The Diasporic Imagination of Old Colony Mennonites in Mexico, 1930-1950.”